Variability of specific needle area in Pinus pinea L. with environment resources availability: light, water and nutrients - Correia A.C.; Mutke S.; Silva J. (Mediterranean pine nuts from forests and plantations, 2017)
Specific Leaf Area (Specific Needle Area, SNA in “needle shape” leaves) is a measure of leaf thickness. It is used for scaling physiological processes measured at the leaf and shoot scale to the whole-tree foliage, being closely related with species strategy to acquire and use resources. The main objective of this study was to gather a database of SNA values for stone pine collected in different time periods for Portugal and Spain and analyse the relationships between SNA and environmental conditions during needles growth. We analysed the variability of SNA within the tree and between trees from different ecological regions and studied the effect of: (i) hydrological years, (ii) light growing conditions within the crown and (iii) the combined effects of water and nutrients. Mean SNA values under natural conditions, taking all sites together, was 32.9 ± 1.2 cm2/g. Higher SNA values were found in needles developed during dry years, in needles growing under low light conditions and under higher nutrients and water availability. We conclude that water availability during needle development is an important driver of SNA variability within and between trees. In order to establish accurate leaf area to dry mass ratios for stone pine and to minimize the errors of scalling-up processes from the leaf to the stand level, more studies are required for other regions and environment conditions.
2. International Meeting on Mediterranean Stone Pine for Agroforestry : AgroPine2016, 2016/05/18-20, Oeiras (Portugal)